O acervo pictórico da Igreja de São Sebastião em Manaus - Rodrigues, Carrie Carolinne Evans Ferreira (2016)
This academical search has for obtaining develop a study on the pictorial collection at Igreja de São Sebastião (St. Sebastian Church) by means of iconography and iconology, looking for both give rise to the information referring to this aggregation that takes part on a collection which has historical prominence, and arrange such information out methodically. After the pictorial collection has been identified and documented visually, an aesthetical appreciation was done, intending to analyze techniques, themes, and features of the composition. The method which has been employed involved the historical research and the iconographic analysis in accordance to Panofsky´s theoretical prescriptions (Panofsky, 1991). Also, it was done the identification of the motifs, of the themes and iconographic features of the paintings which were selected from the nave, the transept, the ceiling, the high altar and the cupola of the Igreja de São Sebastião. These works were made under the supervision of the Italian architect Silvio Centofanti. The Igreja de São Sebastião had already been studied in its architectural aspects (Mesquita, 1999) and had already appeared among a list of old churches that form a touristic and patrimonial itinerary at Manaus city (Andrade, Filippini, 2009). The consummation of this iconographic study is unprecedented, and proposes contribution by offering historic-artistic subsidies for the history of art in Amazonas. Key-words: Painting – Manaus – Sacred iconography – Silvio Centofanti – Igreja de São Sebastião (St. Sebastian Church) – Francesco Campanela.